Monitoring of radiofrequency thermal ablation in liver tissue through fibre Bragg grating sensors array. Issue 14 (1st July 2014) - Tosi, D.; Macchi, E.G.; Braschi, G.; Gallati, M.; Cigada, A.; Poeggel, S.; Leen, G.; Lewis, E.
Abstract : A fibre Bragg grating (FBG) array‐based sensing probe has been installed on a device for radiofrequency thermal ablation (RFTA). The probe is made of five FBGs with 0.5 cm active area and 1 cm spacing, to provide quasi‐distributed thermal pattern measurements. Multiple experiments have been conducted on porcine liver, reporting the temperature pattern along the ablation axis. Thermal maps allow an estimation of the RFTA efficiency and spatial extension in the liver.